SOSIALISASI PERPAJAKAN MEMEDIASI HUBUNGAN PENGARUH MODERNISASI ADMINISTRASI PERPAJAKAN DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMA KUPANG - Ni Luh Ayu Setiawati; I Komang Arthana; Yemima Eka Christi Windya (Indo-Fintech Intellectuals: Journal of Economics and Business, 2026)
The Indonesian tax system continues to undergo transformation in line with advances in information technology and the increasing demand for efficiency in public administration. As the primary source of state revenue, taxation contributes more than 70% of total government income in the 2019–2023 national budget, making taxpayer compliance a crucial factor for sustaining national development. This study aims to examine the influence of tax administration modernization and tax knowledge on individual taxpayer compliance, with tax socialization serving as a mediating variable.  A quantitative descriptive approach was applied using a survey method involving 72 individual taxpayers registered at the Kupang Primary Tax Office (KPP Pratama Kupang).  Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that both tax administration modernization and tax knowledge exert a positive influence on taxpayer compliance, however, the effect of modernization is positive yet statistically insignificant, whereas tax knowledge demonstrates a positive and significant effect. Within this relationship, tax socialization emerges as an important variable, as it also produces a positive and significant effect on taxpayer compliance, thereby strengthening the overall mechanism for enhancing compliance.  In addition to its direct impact, tax socialization functions as an effective mediating variable that reinforces the influence of tax administration modernization on individual taxpayer compliance.  Nevertheless, socialization does not significantly mediate the relationship between tax knowledge and individual taxpayer compliance.  These findings underscore that the success of digital reforms within the tax system relies heavily on the intensity of tax socialization and public tax literacy.  Consequently, adaptive and digitally driven tax communication strategies must be strengthened by tax authorities to support more effective compliance outcomes.